The Acheulian culture of the Hunsgi Valley (peninsular India) : a settlement system perspective - Paddayya, K. (Deccan College Postgraduate and Research Institute, 1982)
Archaeological and paleontological study of lower palaeolithic occupation of the Hunsgi Valley, Gulbarga District, Karnataka.